Stress Controllability in Thermal and Electrical Conductivity of 3D Elastic Graphene‐Crosslinked Carbon Nanotube Sponge/Polyimide Nanocomposite. (10th April 2019) - Zhang, Fei; Feng, Yiyu; Qin, Mengmeng; Gao, Long; Li, Zeyu; Zhao, Fulai; Zhang, Zhixing; Lv, Feng; Feng, Wei
Abstract: Stress controllability in thermal and electrical conductivity is important for flexible piezoresistive devices. Due to the strength‐elasticity trade‐off, comprehensive investigation of stress‐controllable conduction in elastic high‐modulus polymers is challenging. Here presented is a 3D elastic graphene‐crosslinked carbon nanotube sponge/polyimide (Gw ‐CNT/PI) nanocomposite. Graphene welding at the junction enables both phonon and electron transfer as well as avoids interfacial slippage during cyclic compression. The uniform Gw ‐CNT/PI comprising a high‐modulus PI deposited on a porous templated network combines stress‐controllable thermal/electrical conductivity and cyclic elastic deformation. The uniform composites show different variation trends controlled by the porosity due to different phonon and electron conduction mechanisms. A relatively high k (3.24 W m −1 K −1, 1620% higher than PI) and suitable compressibility (16.5% under 1 MPa compression) enables the application of the composite in flexible elastic thermal interface conductors, which is further analyzed by finite element simulations. The interconnected network favors a high stress‐sensitive electrical conductivity (sensitivity, 973% at 9.6% strain). Thus, the Gw ‐CNT/PI composite can be an important candidate material for piezoresistive sensors upon porosity optimization based on stress‐controllable thermal or electrical conductivity. The results provide insights toward controlling the stress‐induced thermal/electrical conductivities of 3D interconnected templated composite networks for piezoresistive conductors or sensors. Abstract : An elasic, flexible, and stress controllable thermal and electrical conductivity of a graphene‐crosslinked carbon nanotube (Gw ‐CNT)/polyimide (PI) nanocomposite is developed. A Gw ‐CNT network is constructed to provide a continuous conductive network and an elastic template for the rigid PI. The elasticity, thermal conductivity, and electrical conductivity of the resulting composites can be effectively controlled by adjusting the amount of PI.